Implementasi Si Sakti dan Si Bulan Sebagai Renja Pada Dinas Kependudukan Dan Pencatatan Sipil (Disdukcapil) Kota Magelang Tahun 2020 - Yoshandi Rendra Prastya; Suci Nasehati Sunaningsih (Journal of Public Administration and Local Governance, 2020)
The purpose of the research is to find out the implementation of public service innovation in the Civil Population and Recording Office of Magelang. With the public service through the innovation program carried out is expected to increase the achievement in the distribution of death certificates as well as birth certificates. This type of research is qualitative by describing the implementation of SI SAKTI and SI BULAN public service innovations in the Civil Population and Recording Office of Magelang. This type of research is a case study. In data collection used interview and observation techniques. Data analysis techniques use data reduction, data feed and conclusion drawing. The results of the study describing the implementation of public service innovations in the form of SI SAKTI (ready deliver death certificates) and SI BULAN (mother action home carrying birth certificate) showed positive results in the distribution of death certificates and birth certificates according to the Disdukcapil Magelang city, in addition to socialization information about innovations that have been conveyed through the website and the village in the ownership of personal data such as ownership of death certificate and birth certificate. Ownership of personal data increased from the previous month after this innovation was implemented.